Perancangan Aplikasi untuk Tes Diagnosis Gangguan Komunikasi (Afasia) - Danu Satria Wiratama; Hindriyanto Dwi Purnomo (KITA Institute, 2023)
Aphasia is a disorder of the brain that causes sufferers to have difficulty communicating. In diagnosing this disorder, a TADIR test is needed. The TADIR test is actually a diagnostic tool that is carried out manually so it takes a long time to get the results, therefore in this study an application was created to shorten the diagnostic time while saving data automatically into the database so that treatment can be done faster. The stages in this research start from the identification of the problem, which then collects data and continues with the design and manufacture of applications, after the application the last stage is testing and reporting. In designing this application, a MySQL storage system is used which is already integrated with the application. The result of this study is an information system in the form of an aphasia diagnosis test application that can make diagnosis time efficient by 72% compared to using the manual method.